2012
DOI: 10.1681/asn.2011070711
|View full text |Cite
|
Sign up to set email alerts
|

Folate Receptor–Targeted Antioxidant Therapy Ameliorates Renal Ischemia–Reperfusion Injury

Abstract: Antioxidant therapy can protect against ischemic injury, but the inability to selectively target the kidney would require extremely high doses to achieve effective local concentrations of drug. Here, we developed a directed therapeutic that specifically targets an antioxidant to renal proximal tubule cells via the folate receptor. Because a local increase in superoxide contributes to renal ischemic injury, we created the folate-antioxidant conjugate 4-hydroxy-Tempo (tempol)-folate to target folate receptors, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…TEMPOL has been shown to reduce post-ischemic inflammatory signaling in a rat [54] and mouse [57] model of renal I/R and a Guinea pig model of gallbladder I/R [56]. Oxidative stress and cell death during I/R lead to highly pleiotropic immune signaling and sterile inflammation [9], which was confirmed in our model on the basis of the IL-6 ( Figure 3B) and MPO data ( Figure 3G, H).…”
Section: Tempol Reduces Peritubular and Glomerular Neutrophil Influx supporting
confidence: 79%
See 1 more Smart Citation
“…TEMPOL has been shown to reduce post-ischemic inflammatory signaling in a rat [54] and mouse [57] model of renal I/R and a Guinea pig model of gallbladder I/R [56]. Oxidative stress and cell death during I/R lead to highly pleiotropic immune signaling and sterile inflammation [9], which was confirmed in our model on the basis of the IL-6 ( Figure 3B) and MPO data ( Figure 3G, H).…”
Section: Tempol Reduces Peritubular and Glomerular Neutrophil Influx supporting
confidence: 79%
“…Accordingly, numerous studies have shown that TEMPOL reduces I/R AKI in different species, including rats [54]. The antioxidant [55], immunosuppressive [56,57], and AKIameliorating effects of TEMPOL are well-established in I/R AKI. Conversely, relatively little information is available in terms of renal oxygenation, which is critical for renal function [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a folate-antioxidant conjugate (5-hydroxy-Tempo-folate) was synthesized to ameliorate renal ischemia/reperfusion injury (IRI). Such Tempo-folate conjugate was designed to target FRα-highly expressed proximal tubular epithelia, where the predominant site of injury occurred during and after IRI [82]. The third question is how to prevent FA-decorated nanoparticles to be filtered from glomeruli to prolong the circulation time for systemic targeted chemotherapy, perhaps by increasing the size and PEGylation of the nanoparticles.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…In this regard, antioxidants are known to mitigate ischemia-reperfusion injury [44,45]. To limit the non-selective target of antioxidant therapy and to avoid the high dose of antioxidants necessary to achieve effective local concentrations, a research team has recently demonstrated that complexation of the membrane-permeable superoxide dismutase mimetic 4-hydroxy-Tempo (Tempol) to folate specifically targeted the renal proximal tubules, due to their expression of high levels of folate receptors, -and limited ischemia-reperfusion injury [46]. The preservation period represents a critical therapeutic time window.…”
Section: Strategies To Limit Renal Ischemia-reperfusion Injuries and mentioning
confidence: 99%